2018
DOI: 10.1096/fj.201800331r
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial barrier function is differentially regulated by CEACAM1‐mediated signaling

Abstract: Carcinoembryonic antigen-related cell adhesion molecule-1 (CEACAM1) is known to be crucial to vasculogenesis and angiogenesis. Recently, CEACAM1 deficiency was shown to result in the formation of aortic plaque-like lesions, indicating a role for CEACAM1 in adult vessels as well. The underlying mechanisms remained largely elusive. Therefore, we aimed to elucidate the role of CEACAM1 in endothelial homeostasis. Here, we show that CEACAM1 deficiency causes subcellular eNOS redistribution in endothelial cells ( i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…The immunoreaction was detected using peroxidase–antiperoxidase and avidin–biotin complex methods by a modified nickel‐enhanced glucose oxidase technique (Kilic & Ergün, ). Immunoblot experiments were conducted according to a protocol described before (Ghavampour et al., ; Oliveira‐Ferrer et al., ). Primary antibodies used in this study are listed in .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunoreaction was detected using peroxidase–antiperoxidase and avidin–biotin complex methods by a modified nickel‐enhanced glucose oxidase technique (Kilic & Ergün, ). Immunoblot experiments were conducted according to a protocol described before (Ghavampour et al., ; Oliveira‐Ferrer et al., ). Primary antibodies used in this study are listed in .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, CEACAM1 was shown to upregulate the endothelial expression of VEGF and VEGFR‐2 (Kilic et al., ). Furthermore, we have previously shown that in the presence of TNF‐α, CEACAM1 recruits Src kinase to intercellular adhesion sites, thereby promoting the phosphorylation of adherens junction proteins and increasing vascular permeability (Ghavampour et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…GCX covers most mammalian cells. For endothelial cells (ECs), a healthy GCX forms a selective barrier between ECs and their neighboring environment, by blocking adhesion receptors on the endothelium from binding to ligands on cells and certain molecules from the environment (Figure a) . The EC GCX is composed of a variety of sugar chains, glycoproteins, and soluble proteins.…”
Section: Introductionmentioning
confidence: 99%
“…RETN (resistin) is an immune-associated entity and a component of neutrophil exocytic granules (155) and inhibits essential neutrophil functions e.g., the oxidative burst (156). CEACAM1 is expressed on a variety of immune cells (42, 157), including neutrophils (158) and is a key receptor involved in binding of these cells to endothelial cells during the process of exvagination from the periphery into tissue locations (159,160). CDADC1 (cytidine and dCMP deaminase domain containing 1) is reportedly a testis-specific protein involved in testis development (161), however it may play a role in regulating the cell cycle and proliferation (162,163).…”
Section: Gpr84mentioning
confidence: 99%